KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENGIMPLEMENTASIKAN KURIKULUM MERDEKA DI SMP NEGERI 6 SATUI - Priyo Utomo; Husnul Madihah; Aam Gunawan (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
This study aims to analyze the role of the principal’s transformational leadership in the implementation of the Merdeka Curriculum within the school context. The research was conducted at SMP Negeri 6 Satui using a descriptive qualitative approach. The research participants consisted of the principal and various educational stakeholders involved in the management and implementation of educational activities at SMP Negeri 6 Satui. Data were collected through classroom and school observations, in-depth interviews, and document analysis. The findings indicate that: (a) the principal’s transformational leadership functions effectively in fostering a positive work ethic and enhancing the motivation of all school resources, thereby creating institutional readiness for the optimal implementation of the Merdeka Curriculum; (b) the implementation of the Merdeka Curriculum at SMP Negeri 6 Satui has been carried out in a systematic and well-directed manner and demonstrates effective development; and (c) the involvement of parents and the wider community contributes to strengthening synergy in supporting the implementation of the Merdeka Curriculum at the school.